Room temperature ultrafast synthesis of N- and O-rich graphene films with an expanded interlayer distance for high volumetric capacitance supercapacitors. Issue 35 (27th August 2019) - Huang, Cong; Hu, Aiping; Li, Yanhua; Zhou, Haifeng; Xu, Yali; Zhang, Yan; Zhou, Shengping; Tang, Qunli; Chen, Chuansheng; Chen, Xiaohua
Abstract : N- and O-rich graphene films are prepared by the electrochemical functionalization method at room temperature in 60 s. Abstract : An electrochemical functionalization method is developed to fabricate N- and O-rich graphene films (F-RGO-60) with an expanded interlayer distance. In particular, the functionalization process could be completed within 60 seconds at room temperature, which is conducive to large-scale commercial applications. Electrochemical synthesis of F-RGO-60 leads to two synergetic effects simultaneously: (1) the expansion of the interlayer distance caused by a bubble effect, which leads to more exposure of the active surface area and (2) the introduction of N-doped sites and oxygen-containing functional groups, which not only improves the hydrophilicity of F-RGO-60 but also provides extra pseudocapacitance. It is worth mentioning that after electrochemical functionalization, F-RGO-60 can still maintain a high density of 1.47 g cm −3 . Due to their optimal surface area, good electrolyte wettability and massive redox-active sites, the specific capacitance of F-RGO-60 films can reach up to 319.4 F cm −3 (217.3 F g −1 ) at 1 A g −1 in a three-electrode system, which is about 3.6 times larger than that of RGO films (60 F g −1 ). The integration of the low-cost preparation method and outstanding performance suggests that F-RGO-60 has great development prospects as supercapacitor electrode materials.